The poet Omar Ben El-Biskri: his life and poetry - slimani, hakim (El Omda in Linguistics and Discourse Analysis, 2025)
This research paper aims to introduce an obscure poet, Sheikh Omar bin Al-Biskari, one of the men of reform. And standing on his poetry scattered in the national newspapers such as Al-Shihab, Al-Basir and Al-Manar, and examining the contents of this poetry that was walking in the line of reform, and the approach of the Algerian Muslim Scholars Association, such as calling for knowledge and spreading it, praising its men, spending money in its way, urging unity, and rejecting division, Fighting percussive, poverty, ignorance, hatred of colonialism, and yearning for freedom.